Calcium-activated Myosin V closes the Drosophila pupil. - Satoh, A.K.; Li, B.X.; Xia, H.; Ready, D.F. (Current Biology, 2008)
Approximately 40 years ago, an elegant automatic-gain control was revealed in compound eye photoreceptors: In bright light, an assembly of small pigment granules migrates to the cytoplasmic face of the photosensitive membrane organelle, the rhabdomere, where they attenuate waveguide propagation along the rhabdomere. This migration results in a "longitudinal pupil" that reduces rhodopsin exposure by a factor of 0.8 log units. Light-induced elevation of cytosolic free Ca(2+) triggers the migration of pigment granules, and pigment granules fail to migrate in a mutant deficient in photoactivated TRP calcium channels. However, the mechanism that moves photoreceptor pigment granules remains elusive. Are the granules actively pulled toward the rhabdomere upon light, or are they instead actively pulled into the cytoplasm in the absence of light? Here we show that Ca(2+)-activated Myosin V (MyoV) pulls pigment granules to the rhabdomere. Thus, one of MyoV's several functions is also as a sensory-adaptation motor. In vitro, Ca(2+) both activates and inhibits MyoV motility; in vivo, its role is undetermined. This first demonstration of an in vivo role for Ca(2+) in MyoV activity shows that in Drosophila photoreceptors, Ca(2+) stimulates MyoV motility.